2017
DOI: 10.1111/bjh.14708
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma: towards providing a benchmark for the cardiac safety profile of proteasome inhibition in multiple myeloma

Abstract: Summary This retrospective analysis aimed to establish the overall cardiac safety profile of bortezomib using patient‐level data from one phase 2 and seven phase 3 studies in previously untreated and relapsed/refractory multiple myeloma (MM). Seven clinically relevant primary [congestive heart failure (CHF), arrhythmias, ischaemic heart disease (IHD), cardiac death] and secondary (hypertension, dyspnoea, oedema) cardiac endpoints were defined based on MedDRA v16.0 preferred terms. 2509 bortezomib‐treated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…The rate of cardiac events in eVOBs (including cardiac failure, atrial fibrillation, tachycardia NOS, and cardiac failure NOS) was 6%. This is consistent with a retrospective analysis that examined data from almost 4000 patients with RRMM in phase 2 and phase 3 studies and found that bortezomib‐based treatment appeared to have low incidences of cardiac events . Nevertheless, the bortezomib summary of product characteristics section on warnings and precautions mention heart failure and ECG QT‐interval prolongation…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of cardiac events in eVOBs (including cardiac failure, atrial fibrillation, tachycardia NOS, and cardiac failure NOS) was 6%. This is consistent with a retrospective analysis that examined data from almost 4000 patients with RRMM in phase 2 and phase 3 studies and found that bortezomib‐based treatment appeared to have low incidences of cardiac events . Nevertheless, the bortezomib summary of product characteristics section on warnings and precautions mention heart failure and ECG QT‐interval prolongation…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a retrospective analysis that examined data from almost 4000 patients with RRMM in phase 2 and phase 3 studies and found that bortezomib-based treatment appeared to have low incidences of cardiac events. 36 Nevertheless, the bortezomib summary of product characteristics section on warnings and precautions mention heart failure and ECG QT-interval prolongation. 37 Interpretation of data regarding resource utilization is limited due to differences in clinical practice and healthcare systems between the different countries participating in eVOBS.…”
Section: Discussionmentioning
confidence: 99%
“…In the ENDEAVOR (Randomiz e d, ope n label, phase 3 study of carfilzomib plus de xameth a sone v s bortezomib plus dexamethas o ne in patients with r elapsed multiple myeloma) trial, hypertension was reported in 25% of patients receiving combination carfilzomib and dexamethasone with grade 3 or higher CV events occurring in 9% (compared to 3% in the bortezomib treated arm) (Dimopoulos et al , ). Although the specific cardiotoxicities are unclear, these probably do not represent a class‐related effect as recent data suggest low cardiotoxicity associated with bortezomib (Laubach et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several proteasome‐targeting inhibitors (e.g., bortezomib, carfilzomib) have been introduced in the clinic. A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma reported that bortezomib‐based treatment was associated with a low incidence of cardiac events . Epigenetic cancer therapy using histone deacetylase inhibitors is also emerging, as epigenetic gene silencing is a hallmark of cancer cells.…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%